PENGARUH PRODUK, PROMOSI, LOKASI DAN REPUTASI TERHADAP KEPUTUSAN MENABUNG PADA LEMBAGA PERKREDITAN DESA DI KOTA DENPASAR - Yusmini, Ni Made; Emi Tinayanti, Ni Kadek (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2025)
This study was conducted with the aim of determining the influence of products, promotions, locations and reputations on savings decisions at LPD Desa Pakraman Penatih, Denpasar. The methodology used quantitative analysis using questionnaires and interviews, document recording. The population was 2,529 people with a sample of 96 customers of LPD Desa Pakraman Penatih, Denpasar using simple random sampling techniques and 5 hypotheses with analysis tools using SPSS version 26. The results of this study stated that the product significantly influenced savings decisions with a t count of 1.897 with a significance of 0.061. Promotions did not significantly influence savings decisions with a t count of -1.046, a significance of 0.299. Location significantly influenced savings decisions with a t count of -3.964, a significance of 0.000. Reputation significantly influenced savings decisions with a t count of 3.737, a significance of 0.000. Product, promotion, location and reputation simultaneously have a significant influence on saving decisions with a calculated f value of 7.385.